Cloning of nitrate reductase genes from the cyanobacterium Anacystis nidulans. - Kuhlemeier, C J (1984)
Anacystis nidulans, a non-nitrogen-fixing cyanobacterium, can fulfill its nitrogen requirement by the assimilation of nitrate. The first step in the pathway, the reduction of nitrate to nitrite, is catalyzed by the molybdo-protein nitrate reductase. In this study, newly developed techniques for gene cloning in A. nidulans R2 were used for the isolation of two genes involved in nitrate reduction. One gene was cloned by complementation of the corresponding mutant; the other gene was picked up from a cosmid gene library by using a restriction fragment containing the transposon-inactivated gene as a probe. Both genes were unlinked single-copy chromosomal genes. Transformation studies provided evidence for the existence of a third locus involved in nitrate reduction.